El contexto histórico de la formación del Ilustre Colegio de Abogados de Puebla en 1834 (2015)
This article presents a historical overview of the process of education and graduation of lawyers in Puebla, Mexico. It also identifies the discussions that confronted the traditions which housed the chairs of law and the process of political control they experienced. Finally, it presents a reflection on political ties many of the graduates of law schools and their impact on the consolidation of a Mexican native right along the independence century